Strategi Pembelajaran Al-Qur’an secara Daring dalam Meningkatan Kompetensi Peserta Didik Madrasah Ibtidaiyah di Kabupaten Lamongan - Nur Zaini; Zuhriyyah Hidayati; Muhammad Afifuddin (Fakultas Agama Islam Universitas Billfath, 2024)
This research aims to describe teachers' strategies for learning the Al-Qur'an online which began during the Covid-19 Pandemic for MI students in Lamongan, the obstacles they faced and their solutions, as well as analyzing the level of reading and writing skills of MI students in Lamongan. This research is descriptive qualitative field research. The research object is MIS in Lamongan, namely 5% of 240 MIS in 11 sub-districts in Lamongan, namely 12 MIS. The data collection technique uses interviews and documentation. The data analysis uses the Matthew B. Milles & Hubberman model which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the research are, first, an online Al Qur'an learning strategy. At the preparation stage, the teacher prepares lesson plans with adjustments to material, time allocation, methods and media. At the implementation stage, some MIS are implemented fully online via social media, WhatsApp, Zoom, Google Meet and others. Second, obstacles to implementing learning include preparation obstacles, obstacles to Al-Quran learning methods, technical problems and facilities. Third, the competency and ability of the Al-Quran of MI students in Lamongan has decreased. If with offline learning the achievement of learning objectives can reach 80-95% of the target, then with online learning, the average achievement is below 80%.